2021
DOI: 10.3390/min11070777
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Selected Characteristics of Enrichment Products for Regular and Irregular Aggregates Beneficiation in Pulsating Jig

Abstract: Article concerns problem of jig beneficiation of mineral aggregates and focuses especially on problem of separation of hard-enrichable materials. Investigative programme covered tests in laboratory and semi-plant scale and material with different content of regular and irregular particles, along with various particle size fractions, was under analysis. Two patented solutions were utilized as methodological approach and densities and absorbabilities of individual products were determined and major novelty of ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Research [44] showed that irregular granite grains used in special concretes might increase their elasticity. The obtained chalcedonite aggregates and gravel with irregular grains by additional enrichment with water-pulsed jigs allowed the production of aggregates with high porosity and water absorption [45][46][47]. Especially, chalcedonite aggregates with an increased specific surface and porosity are particularly suitable for the production of filters and as a component of raw materials supplied in the burning process (production of lightweight aggregates and cement clinker).…”
Section: Discussionmentioning
confidence: 99%
“…Research [44] showed that irregular granite grains used in special concretes might increase their elasticity. The obtained chalcedonite aggregates and gravel with irregular grains by additional enrichment with water-pulsed jigs allowed the production of aggregates with high porosity and water absorption [45][46][47]. Especially, chalcedonite aggregates with an increased specific surface and porosity are particularly suitable for the production of filters and as a component of raw materials supplied in the burning process (production of lightweight aggregates and cement clinker).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, materials were prepared for separation in the full grain size range, i.e., 2.0-16.0 mm. The exact scheme of preparation for selected fractions of regular and irregular grains is shown in publications [16,44]. Achieving the main research objective made it possible to define guidelines for the regulation of certain work parameters for the newly constructed prototype of a light fraction separator-first in a laboratory scale and then in an industrial scale-to be used in the technological system.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies confirmed these results, which showed that screening of feed material into narrow particle size fractions as well as the separation of these fractions in terms of shape brings more favorable results using pulsating movements to enrich aggregates. This is due to the narrowing of the parameters for the relevant aggregates and the elimination of equally settling particles [16,46].…”
Section: Multivariate Analysis Of the Influence Of Variable Parameter...mentioning
confidence: 99%
See 1 more Smart Citation
“…Отсадка представляет собой один из гравитационных методов обогащения, основанный на расслаивании зерен обогащаемого материала в попеременных восходящем и нисходящем потоках воды [8].…”
Section: анализ оборудования и технологий обогащения щебня из промышл...unclassified